Transfer of Soleus Muscular Branch of Tibial Nerve to Deep Fibular Nerve to Repair Foot Drop After Common Peroneal Nerve Injury: A Retrospective Study - Bao, Bingbo; Wei, Haifeng; Zhu, Hongyi; Zheng, Xianyou (Frontiers in Neurology, 2022)
Objective: Common peroneal nerve (CPN) injury that leads to foot drop is difficult to manage and treat. We present a new strategy for management of foot drop after CPN injury. The soleus muscular branch of the tibial nerve is directly transferred to the deep fibular nerve, providing partial restoration of motor function. Methods: We retrospectively reviewed 8 patients treated for CPN injury between 2017 and 2019. The soleus muscular branch of the tibial nerve was transferred to the deep fibular nerve to repair foot drop. Electrophysiology was conducted, and motor function was assessed. Motor function was evaluated by measuring leg muscle strength during ankle dorsiflexion using the British Medical Research Council (BMRC) grading system and electromyography (EMG). Results: In 10-15 months postoperatively, EMG revealed newly appearing electrical potentials in the tibialis anterior, extensor hallucis longus, and extensor toe longus muscle (N=7). Two patients achieved BMRC grade of M4 for ankle dorsiflexion, 2 patients achieved M3, 1 patient achieved M2, and 2 patients achieved M1. Four patients showed good functional recovery after surgery and could walk and participate in activities without ankle-foot orthotics. Conclusion: Surgical transfer of the soleus muscular branch of the tibial nerve to the deep fibular nerve after CPN injury provides variable improvements in ankle dorsiflexion strength. Despite variable strength gains, 50% of patients achieved BMRC M3 or greater motor recovery, which enabled them to walk without assistive devices.